2019
DOI: 10.3390/ijms20061343
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Light at Night Alleviates the Negative Effect of Pb on Freshwater Ecosystems

Abstract: Artificial light at night (ALAN) is an increasing phenomenon worldwide that can cause a series of biological and ecological effects, yet little is known about its potential interaction with other stressors in aquatic ecosystems. Here, we tested whether the impact of lead (Pb) on litter decomposition was altered by ALAN exposure using an indoor microcosm experiment. The results showed that ALAN exposure alone significantly increased leaf litter decomposition, decreased the lignin content of leaf litter, and alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 50 publications
3
11
0
Order By: Relevance
“…This finding supported the hypothesis that the biological characteristics of the altered microbial community facilitated the ability of the community to cope with Cd toxicity [3]. Interestingly, this is consistent with previous findings that leaf litter decomposition related fungi could form adaptive mechanisms for tolerance to NPs and/or metal ions (e.g., ZnONP, AgNP, and Cu 2+ ) by accumulating dominant species [3,10,28,29].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This finding supported the hypothesis that the biological characteristics of the altered microbial community facilitated the ability of the community to cope with Cd toxicity [3]. Interestingly, this is consistent with previous findings that leaf litter decomposition related fungi could form adaptive mechanisms for tolerance to NPs and/or metal ions (e.g., ZnONP, AgNP, and Cu 2+ ) by accumulating dominant species [3,10,28,29].…”
Section: Discussionsupporting
confidence: 90%
“…These results indicated that ALAN exposure can alter the fungal community structure and composition. This is consistent with the results of recent studies which showed that light radiation not only can alter the fungal community, but also inhibit litter decomposition associated with fungi [8][9][10]. However, our results differ from these studies [8,9] in that effects of different light conditions on the structure and diversity of fungal communities are significantly different.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations